2018
DOI: 10.3390/app8101728
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-ray Generation from ZnO Nanowire Targets in a Non-Relativistic Regime of Laser-Solid Interactions

Abstract: We present a detailed investigation of X-ray emission from both flat and nanowire zinc oxide targets irradiated by 60 fs 5 × 1016 W/cm2 intensity laser pulses at a 0.8 µm wavelength. It is shown that the fluence of the emitted hard X-ray radiation in the spectral range 150–800 keV is enhanced by at least one order of magnitude for nanowire targets compared to the emission from a flat surface, whereas the characteristic Kα line emission (8.64 keV) is insensitive to the target morphology. Furthermore, we provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Quasi-aperiodic arrangement by aligning the non-periodic nanowire array unit cells was introduced to generate a uniformly-shaped emission beam. Meanwhile, Samsonova et al investigated the hard X-ray emission from vertical ZnO nanowires with a different array arrangement as a target irradiated by femtosecond laser pulses [43]. Experiments showed that both ordered and disordered vertical ZnO nanowire targets enhance the fluence of the hard X-ray emission compared to the one from a flat surface target, which supports that vertical nanowire arrays can be utilized in various applications including X-ray spectroscopy.…”
Section: Nanowire Array Arrangementsmentioning
confidence: 99%
“…Quasi-aperiodic arrangement by aligning the non-periodic nanowire array unit cells was introduced to generate a uniformly-shaped emission beam. Meanwhile, Samsonova et al investigated the hard X-ray emission from vertical ZnO nanowires with a different array arrangement as a target irradiated by femtosecond laser pulses [43]. Experiments showed that both ordered and disordered vertical ZnO nanowire targets enhance the fluence of the hard X-ray emission compared to the one from a flat surface target, which supports that vertical nanowire arrays can be utilized in various applications including X-ray spectroscopy.…”
Section: Nanowire Array Arrangementsmentioning
confidence: 99%
“…The abnormal spectral distortion is not a specific phenomenon for this particular CCD, therefore it can be generalized to different CCD detector types. Firstly, the abnormal spectral distortion of Compton scattering electrons also exists in high-Z sensor-based CCDs of GaAs and CdTe, which have been developed recently to cover the 8-800 keV x-ray energy range [18,19]. The Compton scattering will be more serious at the harder x-ray range covered by high-Z sensor-based CCDs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by carefully controlling growth conditions, one can also obtain disordered nanowires. It is shown that foams composed of disordered nanowires are more robust to laser field polarization as compared with aligned ones in the case of nonrelativistic interactions [41]. It also relaxes requirements on the calibration of laser systems.…”
Section: Introductionmentioning
confidence: 97%